The Stability of the Competitive System which contains Gross Complementary Goods - Sato, R. (Review of Economic Studies, 1972)
Journal Article The Stability of the Competitive System which contains Gross Complementary Goods Get access Ryuzo Sato Ryuzo Sato Brown University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 495–499, https://doi.org/10.2307/2296518 Published: 01 September 1972